2006
DOI: 10.1007/s00232-006-0860-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology of Turgor Regulation in Marine Siphonous Green Algae

Abstract: Abstract. We review electrophysiological measures of turgor regulation in some siphonous green algae, primarily the giant-celled marine algae, Valonia, and Ventricaria, with particular comparison to the well studied charophyte algae Chara and Lamprothamnium. The siphonous green algae have a less negative plasma membrane potential, and are unlikely to have a proton-based chemiosmotic transport system, dominated by active electrogenic K + uptake. We also make note of the unusual cellular structure of the siphono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 83 publications
(148 reference statements)
1
17
0
Order By: Relevance
“…The Na + versus H + powered-transport in, respectively, marine and freshwater/terrestrial organisms, is however not an absolute rule. For example, the freshwater chlorophyte Ankistrodesmus braunii requires Na + for the transport of PO43, while Charales living in brackish waters typically use H + symporters for nutrient transport (Ullrich and Glaser, 1982; Bisson et al, 2006). The strong negative membrane potential of characean cells is thought to enable H + -symport even in alkaline environments (Bisson et al, 2006).…”
Section: Uptake Of Nitrogen Using Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…The Na + versus H + powered-transport in, respectively, marine and freshwater/terrestrial organisms, is however not an absolute rule. For example, the freshwater chlorophyte Ankistrodesmus braunii requires Na + for the transport of PO43, while Charales living in brackish waters typically use H + symporters for nutrient transport (Ullrich and Glaser, 1982; Bisson et al, 2006). The strong negative membrane potential of characean cells is thought to enable H + -symport even in alkaline environments (Bisson et al, 2006).…”
Section: Uptake Of Nitrogen Using Transportersmentioning
confidence: 99%
“…For example, the freshwater chlorophyte Ankistrodesmus braunii requires Na + for the transport of PO43, while Charales living in brackish waters typically use H + symporters for nutrient transport (Ullrich and Glaser, 1982; Bisson et al, 2006). The strong negative membrane potential of characean cells is thought to enable H + -symport even in alkaline environments (Bisson et al, 2006). Notably, Charales are also able to use Na + -coupled transport for PO43, urea and Cl - (Sanders et al, 1985; Walker et al, 1993; Reid et al, 2000).…”
Section: Uptake Of Nitrogen Using Transportersmentioning
confidence: 99%
“…Transplant experiments with the giant-celled Acetabularia, conducted by Joachim Hämmerling, demonstrated that the nucleus of a cell contains the genetic information that directs cellular development, and postulated the existence of messenger RNA before its structure was determined (Hämmerling, 1953). Acetabularia, along with other giant-celled green algae (Valonia, Chara and Nitella), has also served as an experimental organism for electro-physiological research and studies of cell morphogenesis (Menzel, 1994;Mandoli, 1998;Shepherd et al, 2004;Bisson et al, 2006;Mine et al, 2008). The charophyte Mougeotia played a key role in outlining the role of phytochrome in plant development (Winands & Wagner, 1996).…”
mentioning
confidence: 99%
“…While potassium ion flux has been identified as mainly responsible for turgor regulation (Bisson et al 2006), the molecular details of osmotic regulation have not been resolved. Microalgae osmoregulate mainly through the use of contractile vacuoles (Heywood 1978;Buchmann and Becker 2009) and some accumulate compatible osmolytes like glycerol (Avron 1986;Husic and Tolbert 1986), and in some cases mannitol (Iwamoto and Shiraiwa 2005).…”
Section: Microalgaementioning
confidence: 99%